Planejamento de aula e o uso de Tecnologias da Informação e Comunicação: percepção de docentes do Ensino Médio - Arruda, Heloisa Paes de Barros (2012)
This study has as its objective to gauge the adequacy and efficiency of class planning done by teachers for the effective use of Information and Communication Technology (ICT) in the classroom, and to present indicators of class planning characteristics that encourage the use of information and communication technology in integration with learning situations. In terms of methodological procedures, the case study type of research was chosen, with the participation of seven high school teachers from three different public schools in the state of São Paulo. Semi-structured interviews were chosen as the data-gathering tool, and content analysis was employed for interpreting the data. It was noted that there is a nascent body of literature on the topic of Class Planning and the Use of Information and Communication Technology. The theoretical references on class planning are based on José Fusari, Henri Wallon, José Libâneo, Celso Vasconcellos, Sacristán and Gómez, while those for Information and Communication Technology draw from authors such as Álvaro Vieira Pinto, Fernando J. de Almeida, Maria Elizabeth Almeida, Maria da G. Silva, and Fernando Costa, among others. Thus, this thesis proves the importance of recognizing, diligently preparing, implementing, and monitoring class planning, and the plan, i.e., the respective document, as fundamental elements in mobilizing teachers towards incorporating ICT into their pedagogical routine and, consequently, achieving ongoing improvement in the quality of student education. It was noted that the class planning process is inadequate and inefficient, owing to a number of variables (inadequate working conditions, lack of time, low pay, infrequent feedback from coordinators, lack of infrastructure), and still without a written record of class plans, since they are registered only in undocumented and informal thought form. We noted rather primitive, non-integrated, and unfocused use of ICT as a support in classes. The study shows that the steps in a rigorous, discerning, and careful class planning process, as well as a written plan, combine into a syncretic whole, regardless of whether the plan is or is not followed during the class. Thus we conclude that the curricular act of class planning, when performed inadequately, without systematic recording, syncretically and without replanning, is inefficient, obscures the sense behind the use of ICTs, and fails in encouraging their integrated and consistent use in teaching and learning situations